Islamic Education through Religious Moderation for the Development of National Character - Fajrin, Megawati (Universitas Al-Amien Prenduan, 2024)
This study aims to: 1) identify the forms of religious moderation instilled at MTs Negeri 3 Pamekasan in building national character; 2) identify factors influencing students’ enthusiasm for religious moderation; and 3) analyze the implications of religious moderation for shaping students' national character. This study employs a qualitative approach with field research as its method. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data presentation, conclusion drawing, and data verification. The findings indicate that religious moderation is fostered through school culture (such as habits promoting good manners), student orientation programs (MATSAMA), intra- and extracurricular activities (e.g., ceremonies, scouting, and social services), and an integrated curriculum. Supporting factors include the pesantren environment, school culture, family support, and positive relationships within the school community. The implications of religious moderation include fostering mutual respect, unity, cooperation, empathy, and strengthening students' moral values and social behavior.